Development and Evaluation of Mango Grader - Badhe, V T; Singh, Pratap; Bhatt, Y C (Journal of Agricultural Engineering, 2011)
A computerized grading machine was developed and evaluated to grade Alphonso mangoes on weight basis in five grades. A logistic software was developed to run the grader. The performance of the grader was evaluated at four speeds (480, 600, 720 and 840 m/s), four microprocessor settings (B1, B2, B3 and B4) and their effect was observed on five grades of mango viz., Grade I (326-375 g), Grade II (276-325 g), Grade III (226-275 g), Grade IV (176-225g) and Grade V (&lt 175 &gt 376 g) for single lane. The statistically analyzed data showed maximum capacity of 950 kg/h with maximum grading efficiency of 95.13% at 720 m/s speed and B4 setting. The cost of manual grading was Rs. 350/t as against Rs. 190/t for the grader.